Analysis of the Needs and Development of Health Service Personnel at the Simalingkar Health Center in Medan City - Indah Doanita Hasibuan; Frety Salma Annisa; Rezeky Aulia Ramadhani; Cindy Monica Aulia; Dini Sintia (PROMOTOR, 2024)
The need and development of health service personnel as an integral part of health development is directed to meet the needs of the number and type of qualified health workers in providing all kinds of health service needs. This study aims to determine the needs of health workers both quantity and quality at the Simalingkar Health Center in Medan City.  This research includes Descriptive Research with a qualitative approach, to find and obtain information about the analysis of energy needs at the Simalingkar Health Center in Medan City. The data and information obtained are then compared with the capabilities currently possessed with those expected for planning managers in the preparation of labor analysis of each work unit associated with the description and specifications of work at the Simalingkar Health Center in Medan City. The types of data used in this study are primary data and secondary data. Primary data are obtained through interviews and observations, while secondary data are obtained through tracing official records (documentation). The results showed that the preparation of health worker planning has been carried out so that the analysis of energy needs both in quantity and quality has been well planned. The number of health workers for the implementation of health services is quite sufficient at the Simalingkar Health Center in Medan City. Where health service personnel at Puskesmas have met the standards, or by the Minister of Health Regulation Number 75 of 2014. That way, the needs and development of health workers are well implemented.